Front Cover Picture: Organocatalytic Enantioselective Friedel–Crafts Alkylation/Lactonization Reaction of Hydroxyindoles with Methyleneoxindoles (Adv. Synth. Catal. 5/2018). Issue 5 (8th February 2018) - Xiao, Mengjie; Xu, Dengfeng; Liang, Weihong; Wu, Wenyu; Chan, Albert S. C.; Zhao, Junling
Abstract : The front cover picture, provided by Junling Zhao and co‐workers, illustrates an organocatalytic enantioselective protocol for the Friedel–Crafts alkylation/lactonization reaction of hydroxyindoles with methylene oxindoles. This reaction was efficiently catalyzed by a Cinchona alkaloid‐derived squaramide catalyst, affording the corresponding pyrrolodihydrocoumarin derivatives in moderate to high yields with high enantioselectivities. More importantly, this paper shows an efficient strategy for the regioselective functionalization of the indole benzene positions. Details can be found in the full paper on pages 917–924. (M.‐J. Xiao, D.‐F. Xu, W.‐H. Liang, W.‐Y. Wu, A. S. C. Chan, J.‐L. Zhao, Adv. Synth. Catal .2018, 360, 917–924; DOI:10.1002/adsc.201701089 )